Application of Narrative Nursing Combined With Focused Solution Model to Anxiety and Depression in Patients With Lung Tumor During Perioperative Period - Feng, Jing; Ge, Ling; Jin, Fengxia; Jiang, Li (Frontiers in Surgery, 2022)
In the face of the dual pressure of disease and operation, patients with lung tumors in the perioperative period often have adverse psychological states such as anxiety and depression. There are many risk factors affecting the psychological state of patients in the perioperative period, and there is still a lack of effective nursing countermeasures in clinical practice. We accessed our institutional database and retrospectively selected all patients with lung tumors who underwent surgical treatment between August 2018 and December 2018. Multivariate Logistic regression model was used to analyze the risk factors affecting the psychological state of patients during the perioperative period, and the HAD score, medication behavior, INR monitoring behavior and life behavior before and after narrative nursing combined with focused solution model nursing were compared with those of patients receiving conventional nursing plan. Income status, sleep quality, fear of postoperative pain, Patient's knowledge of their condition and nature of tumor are the independent risk factors affecting the psychological state of patients with lung tumor during perioperative period. Narrative nursing combined with focused solution model can effectively improve the anxiety and depression status of patients with lung tumor during perioperative period and enhance their compliance behavior, which is worthy of promotion.